A phase 3, open-label, controlled, randomized, multicenter trial evaluating the efficacy and safety of StrataGraft® construct in patients with deep partial-thickness thermal burns. Issue 5 (August 2021) - Gibson, Angela L.F.; Holmes, James H.; Shupp, Jeffrey W.; Smith, David; Joe, Victor; Carson, Joshua; Litt, Jeffrey; Kahn, Steven; Short, Tracee; Cancio, Leopoldo; Rizzo, Julie; Carter, Jeffrey E.; et al.
Highlights: StrataGraft treatment eliminated donor tissue harvest in all but 3 of 71 patients. At Month 3, 92% of StrataGraft treatment sites achieved durable wound closure. Donor-site pain was a favorable outcome of significantly reduced autograft use. Cosmesis at StrataGraft/autograft treatment sites were clinically similar at Month 12. The most common treatment-related adverse event was pruritis, which occurred in 11 patients. Abstract: Objective: This phase 3 study evaluated StrataGraft construct as a donor-site sparing alternative to autograft in patients with deep partial-thickness (DPT) burns. Methods: Patients aged ≥18 years with 3–49% total body surface area (TBSA) thermal burns were enrolled. In each patient, 2 DPT areas (≤2000 cm 2 total) of comparable depth after excision were randomized to either cryopreserved StrataGraft or autograft. Coprimary endpoints were: the difference in percent area of StrataGraft treatment site and autograft treatment site autografted at Month 3 (M3), and the proportion of patients achieving durable wound closure of the StrataGraft site without autograft at M3. Safety assessments were performed in all patients. Efficacy and safety follow-up continued to 1 year. Results: Seventy-one patients were enrolled. By M3, there was a 96% reduction in mean percent area of StrataGraft treatment sites that required autografting, compared with autograft treatment sites (4.3% vs 102.1%, respectively; P  < .0001). StrataGraft treatment resulted in durable wound closure at M3 without autografting in 92% (95% CI: 85.6, 98.8; n/n 59/64) of patients for whom data were available. The most common StrataGraft-related adverse event was pruritus (15%). Conclusions: Both coprimary endpoints were achieved. StrataGraft may offer a new treatment for DPT burns to reduce the need for autografting. Clinical Trial Identifier: NCT03005106 .